This man must die - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Buck Trammel western, 2023)
"'In the world of criminal lawbreakers in Laramie County, Lucien Clay was king. He terrorized the locals, robbed every business in the territory, and ruled the place with a merciless iron fist. Thankfully he's behind bars now -- along with a load of other lowlife prairie rats -- thanks to Laramie's new sheriff, Buck Trammel. Unfortunately, Trammel can only enforce the law while others specialize in working around it: namely, lawyers. And no lawyer is more crooked or corrupt than the belly-crawling snake Clay hired to get him out. By any means possible. Their breakout plan is simple: The lawyer will wait until midnight. Then he'll break in to the county jail to bust his client out. He'll scale the walls, kill the guards, ambush the deputies, and release the prisoner. There's just one catch: As soon as Clay is freed, the other convicts want out, too. Which sparks total chaos in the prison, creates a distraction for Clay -- and unleashes the worst blood-soaked night of murderous mayhem Buck Trammel has ever witnessed. And will never forget. If he survives." -- Amazon.